Expression of FIBCD1 by intestinal epithelial cells alleviates inflammation-driven tumorigenesis in a mouse model of colorectal cancer - Shahgoli, Vahid Khaze; Dubik, Magdalena; Pilecki, Bartosz; Skallerup, Sofie; Schmidt, Sandra Gaedt; Detlefsen, Sönke; Sorensen, Grith L.; Holmskov, Uffe; Baradaran, Behzad; Moeller, Jesper B. (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) ranks as the third most prevalent cancer worldwide, highlighting the urgent need to address its development. Inflammation plays a crucial role in augmenting the risk of CRC development and actively contributes to all stages of tumorigenesis. Consequently, targeting early inflammatory responses in the intestinal tract to restore homeostasis holds significant potential for innovative therapeutic strategies against CRC. In this study, we employ transgenic mice that mimic human expression of Fibrinogen C domain containing 1 (FIBCD1), a chitin-binding transmembrane protein primarily present on intestinal epithelial cells (IECs). Previous research has highlighted FIBCD1's ability to effectively suppress inflammatory responses and foster tissue homeostasis at mucosal barriers. Using the azoxymethane/dextran sodium sulfate mouse model, we demonstrate that FIBCD1 substantially impacts CRC development by significantly reducing intestinal inflammation and suppressing colorectal tumorigenesis. Moreover, we identify a soluble variant of FIBCD1, which is significantly increased in fecal matter during acute inflammation. Together, these findings suggest that FIBCD1 has the potential to be a novel molecular target in the context of colitis-associated colorectal cancer and emerges as an intriguing candidate for future research.